Potential Immunoregulatory and Antiviral/SARS-CoV-2 Activities of Nitric Oxide - Stefano, George B; Esch, Tobias; Kream, Richard M (Medical science monitor, 2020)
Nitric oxide (NO) represents a key signaling molecule in multiple regulatory pathways underlying vascular, metabolic, immune, and neurological function across animal phyla. Our brief critical discussion is focused on the multiple roles of the NO signaling pathways in the maintenance of basal physiological states of readiness in diverse cell types mediating innate immunological functions and in the facilitation of proinflammatory-mediated adaptive immunological responses associated with viral infections. Prior studies have reinforced the critical importance of constitutive NO signaling pathways in the homeostatic maintenance of the vascular endothelium, and state-dependent changes in innate immunological responses have been associated with a functional override of NO-mediated inhibitory tone. Accordingly, convergent lines of evidence suggest that dysregulation of NO signaling pathways, as well as canonical oxidative effects of inducible NO, may provide a permissive cellular environment for viral entry and replication. In immunologically compromised individuals, functional override and chronic rundown of inhibitory NO signaling systems promote aberrant expression of unregulated proinflammatory pathways resulting in widespread metabolic insufficiencies and structural damage to autonomous cellular and organ structures. We contend that restoration of normative NO tone via combined pharmaceutical, dietary, or complex behavioral interventions may partially reverse deleterious physiological conditions brought about by viral infection linked to unregulated adaptive immune responses.
Keywords: Nitric Oxide; zánět; antivirové látky; oxidace-redukce; signální transdukce; virus SARS; Animals; Antiviral Agents; lidé; oxid dusnatý; Inflammation; Oxidation-Reduction; Severe acute respiratory syndrome-related coronavirus; Humans; zvířata; Signal Transduction